2021
DOI: 10.1007/s40789-021-00441-5
|View full text |Cite
|
Sign up to set email alerts
|

Coal-derived humic acid for application in acid mine drainage (AMD) water treatment and electrochemical devices

Abstract: In this research work, isolation of humic acid from coal of Northeastern region of India is reported. The study is also targeted for application of the coal-derived humic acid in acid mine drainage (AMD) water treatment and electrochemical devices. All the obtained results are compared with the standard humic acid and examined the formation of humic acid from the coal. The isolated coal-derived humic acid is found to be high degree of humifications and relatively stable up to about 200 °C. The FTIR study indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…7a, it is observed that the CV curve of the carbon dot solution has an irreversible reduction peak at cathode −0.4 V without an oxidation peak and is also symmetric, revealing the stable capacitive behavior of wsCDs. 25,[44][45][46] The results also showed that the cathodic peaks are similar at the same potential windows with varied scan rates, indicating that the electron transfer kinetics is irreversible. [47][48][49] So, the electrolytes made of wsCDs show irreversible reduction at cathodic potentials due to the absence of the complete redox couple.…”
Section: Electrochemical Application Of the Pm-derived Cnsmentioning
confidence: 99%
“…7a, it is observed that the CV curve of the carbon dot solution has an irreversible reduction peak at cathode −0.4 V without an oxidation peak and is also symmetric, revealing the stable capacitive behavior of wsCDs. 25,[44][45][46] The results also showed that the cathodic peaks are similar at the same potential windows with varied scan rates, indicating that the electron transfer kinetics is irreversible. [47][48][49] So, the electrolytes made of wsCDs show irreversible reduction at cathodic potentials due to the absence of the complete redox couple.…”
Section: Electrochemical Application Of the Pm-derived Cnsmentioning
confidence: 99%
“…FTIR spectra of humic acid derived from native (raw) coal and HNO 3 treated coal were obtained to determine the structural changes and presence of functional groups in the produced humic acid [27,28].…”
Section: Ftir Analysismentioning
confidence: 99%
“…Good adsorptive properties of LRC have aroused intense interest for its potential as a versatile environmental adsorbent. The utilization of the coal-based HS in soil remediation [45,[62][63][64] and water treatment systems (municipal wastewater and acid mine drainage) [65][66][67] are recently well-documented. Detoxification studies by research groups led by Qi and by Skłodowski [58,68] have employed LRC as an attractive low-cost adsorbent for the removal of different pollutants from the aquatic and terrestrial environments.…”
Section: Effects Of Lrc On Soil Heavy Metals and Other Pollutantsmentioning
confidence: 99%